Analysis on Environmental and Economic Benefit of Activities in Coal Mined Area: A Case Study of Tanjung Enim Mining Site, South Sumatera - Nunsi Bella Pranatiwi; Bakti Setiawan (ARRUS Journal of Social Sciences and Humanities, 2023)
Tanjung Enim Mining Site, the third oldest coal mining site in Indonesia, has conducted several reclamation activities. However, the leading way to manage the barren areas for both the environmental and economic perspectives is undefined. This research aims to determine the best reclamation activity in the mined-area by having environment and economic comparison through Life Cycle Assessment and cost-benefit analysis. The data is collected through company and government documents, also mining employee’s interviews. The assessed scenarios include revegetation; agriculture (oil-palm plantation), and solar panel field. Based on this study, it results in agriculture (oil-palm plantation) as the most feasible and suitable option to be performed in the coal-mined area for both environment and economic aspects though the revegetation gives the modest environment.